Effects of chilled storage and cryopreservation on sperm characteristics, antioxidant enzyme activities, and lipid peroxidation in Pacific cod Gadus macrocephalus - 王学颖 史雪辉 柳意樊 于道德 官曙光 刘清华 李军 (中国海洋与湖沼学报：英文版, 2016)
The present study evaluated the ef fects of chilled storage and cryopreservation on sperm motion characteristics, antioxidant enzyme activities, and lipid peroxidation in the Pacific cod Gadus macrocephalus. Sperm motility and the activities of superoxide dismutase（SOD）, catalase（CAT）, glutathione peroxidase（GPx）, glutathione reductase（Gr）, and lipid peroxidation（measured via malondialdehyde（MDA） content） were determined after the milt was stored at 4°C for 12 h, cryopreserved without cryoprotectant in 12% propylene glycol（PG）, cryopreserved in 12% PG＋0.1 mol/L trehalose, or cryopreserved in 12% PG spermatozoa but centrifuged to decant the supernatant prior to cryopreservation（only sperm cells were cryopreserved）. After chilled storage or cryopreservation, the SOD, CAT and GPx activities were reduced in sperm cells and increased in seminal plasma in almost all treatments; sperm motility parameters were also decreased. However, the addition of trehalose into the cryoprotectant could signifi cantly improve the postthaw sperm quality as revealed by the sperm average path velocity. This improvement might be attributed to the function of trehalose in scavenging reactive oxygen species. Chilled storage and cryopreservation had signifi cant eff ects on sperm motion characteristics, antioxidant enzyme activities, and lipid peroxidation in the Pacific cod.